(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The paper emphasizes the leading role of informatization of education in the global process of digitalization of the economy of modern society. The characteristic features of the informatization of education, the possibilities and problems of introducing innovative teaching technologies are noted. Attention is drawn to the main directions of this process, and the emerging most important tasks of the formation and development of information and educational environments for open and distance learning. Some results are given regarding models of distance education and the development of automated information and educational systems for educational institutions.